Women and The Granting of Permission to Polygamy (Study of Decision Number 1167/Pdt.G/2022/PA.Kra ) - Kurnianingsih, Marisa; Berlianti, Soffana Zamzam; Zuhdi, Syaifuddin; Amiludin, A; Windiani, Arovah (Prosiding University Research Colloquium, 2023)
This paper will discuss women, namely the rights of the wife, in consideration of the judge who gave permission for polygamy in Decision No. 1167/Pdt.G/2022/PA.Kra. The decision issued by the Karanganyar Religious Court provides several considerations related to the condition of the wife and husband and the continuity of the household after polygamy. This article was written with the aim of knowing how to fulfill women’s rights in the judge’s consideration in decision number 1167/Pdt.G/2022/PA.Kra. The approach method used is the normative-juridical method. Based on the results of the discussion, it can be seen that the judge in Decision Number 1167/Pdt.G/2022/PA.Kra has considered several aspects of fulfilling the rights of wives and husbands and maintaining the continuity of the household by minimizing disputes in the future by determining mutual assets and has considered the financial capabilities of the husband, even though the decision has not shown clarity on the amount of income that the first wife will receive as a guarantee that the husband can act fairly. and in his consideration, the judge set aside several facts that had been submitted in the application and proved that there was an application for a polygamy permit, namely that the prospective second wife was already pregnant. The novelty of this paper is that the author sees several aspects of judges’ considerations in granting permission for polygamy.